How Big Data Analytics Influences Financial Decisions in ASEAN Companies? - Vernard Indranata Pontjoharyo (PT Advanced business journal, 2026)
Abundant streams of complex information have fundamentally transformed how various sectors, particularly corporate finance, approach strategic choices. Within ASEAN capital markets, organizations currently face mounting pressure to implement data-centric frameworks that refine their financial oversight. Utilizing big data analytics provides a significant opportunity to sharpen predictive accuracy, streamline investment tactics, and mitigate risks with greater precision. This research seeks to investigate how big data adoption influences financial choices across ASEAN markets, specifically looking at how data-driven insights boost operational efficiency and bottom-line results. This study adopts a mixed-methods design, integrating quantitative assessments of financial records from ASEAN-listed firms with qualitative perspectives gathered from executive interviews. Findings reveal a clear positive correlation between the integration of advanced analytics and superior financial outcomes, especially regarding market projections, risk control, and the distribution of assets. Entities that successfully embed these analytical tools into their core financial strategies demonstrate stronger performance regarding overall profitability and value for shareholders. Ultimately, big data analytics serves as a vital catalyst for enhancing corporate financial strategies in ASEAN, granting firms a distinct competitive advantage within a fast-paced global economic landscape.